Analisis Pengaruh Kualitas Pelayanan Publik terhadap Kepuasan Masyarakat - Sulaiman Sulaiman; Sunarsih Sunarsih; Desvira Zain (Eksos, 2022)
In accordance with Pontianak Mayor Regulation Number 20.1 of 2021, the Technical Implementation Unit of the Pontianak City Center for Science, Technology and Language has the main task of assisting the Head of the Service in carrying out certain operational activities and/or technical support activities in the fields of Science, Technology and Language. Has the function of carrying out activities according to the scope of its technical work, implementing the services of the Center for Science, Technology and Language according to the scope of its duties, reporting on the implementation of activities according to the scope of its technical work; and carrying out other tasks assigned by the Head of Service. In this study, there are 2 objectives, 1) To determine the effect of the quality of English course services on people's satisfaction at the UPT Center for Science, Technology and Language of Pontianak City. 2) Knowing the sub-variables of the quality of English course services that have a dominant influence on community satisfaction at the UPT Center for Science, Technology and Languages of Pontianak City. The results achieved in this study, 1) The effect of service quality on community satisfaction in the service of the English language course at the UPT Center for Science, Technology and Language of Pontianak City. Service Quality variable partially has a positive and significant effect on Community Satisfaction 2) Service quality subvariable which has a dominant influence on community satisfaction in English Course Services at UPT Center for Science, Technology and Language Pontianak City is Punctuality.